Pembuatan Sabun Padat Transparan Menuju Santri yang Memiliki Jiwa Kewirausahaan - Prasetiyo, Andri; Yantih, Novi; Yamin, Muhamad; Hutagaol, Lungguk; Nawasiah, Nana (FEB-UP Press, 2022)
Community service on counseling and assistance in making solid soap has been carried out at the Al-Amien Islamic Boarding School, Tangerang. This activity was attended by students and junior high school students, senior high school students and the general public. Participants were given knowledge and training regarding the process of preparing, manufacturing, storing and marketing transparent solid soap digital products from palm kernel oil. The quality of the transparent solid soap produced will be tested and compared with the transparent solid soap on the market. This activity is expected to increase the entrepreneurial spirit of the santri so that it can be an opportunity to start a business and meet the soap needs in Islamic boarding schools. This activity is carried out online and offline in the form of workshops with counseling/lectures and practices. This activity needs to be monitored, mentoring and mentoring for future businesses. The resulting transparent solid soap has a pH of 8.43-8.45, a hardness of 34.3-34.4 10-1mm, water content 21.45-21.89%, free fatty acids 0.94-0.98% and 1.74- 1.95%. Transparent solid soap made to meet quality requirements and in accordance with transparent comparison soaps on the market. Keywords: community service, transparent solid soap, palm kernel oil